Staging, risk assessment and screening of breast cancer - Yalcin, B. (Experimental Oncology, 2013)
Breast cancer is the most common female malignant disease in the western countries where a woman's lifetime risk of developing the disease is more than 10 %. Nulliparity or use of hormonal replacement therapy, strong family history, or a history of therapeutic thoracic radiation are considerable high risk factors for the development of breast cancer. Nowadays more new effective therapeutic agents have been developed for the intervention of the breast cancer, but prognosis is still remained poor in the metastatic disease. For the general population, screening mammography in women older than 40 - 45 years has been shown to be effective in identifying early-stage breast cancer and in decreasing the mortality rate. In randomized screening mammography trials for breast cancer, it has been established that screening mammograms reduced breast cancer mortality in women older than 50 years of age by 25 to 30%. This review article summarizes the risk factors for developing breast cancer, methods for risk assessment and the accepted screening guidelines.